2011
DOI: 10.2147/ijn.s18535
|View full text |Cite
|
Sign up to set email alerts
|

Polyanionic carbohydrate doxorubicin–dextran nanocomplex as a delivery system for anticancer drugs: in vitro analysis and evaluations

Abstract: This study deals with the preparation and investigation of a nanoscale delivery system for the anticancer drug doxorubicin (DOX) using its complexation with polyanionic carbohydrate dextran sulfate (DS). Dynamic light scattering, SEM, and zeta potential determination were used to characterize nanocomplexes. DOX-DS complexation was studied in the presence of ethanol as a hydrogen-bond disrupting agent, NaCl as an electrostatic shielding agent, and chitosan as a positively charged polymer. Thermodynamics of DOX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 46 publications
(11 reference statements)
3
5
0
Order By: Relevance
“…These features seem to point out that additional forces are involved in the formation of the conjugate. In agreement with what was reported for DOX - DS conjugates [ 30 ], beyond electrostatic interactions, π - π stacking between drug and DS , together with some additional hydrogen bonding, may also occur (see below for further comments). In particular, π - π stacking can be significantly more marked in the case of 3 with respect to the other complexes, justifying its higher loading.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These features seem to point out that additional forces are involved in the formation of the conjugate. In agreement with what was reported for DOX - DS conjugates [ 30 ], beyond electrostatic interactions, π - π stacking between drug and DS , together with some additional hydrogen bonding, may also occur (see below for further comments). In particular, π - π stacking can be significantly more marked in the case of 3 with respect to the other complexes, justifying its higher loading.…”
Section: Resultssupporting
confidence: 89%
“…A similar scenario, associated with the presence of multiple interaction forces, was indeed observed for DOX-DS [ 30 ].…”
Section: Resultssupporting
confidence: 69%
“…A necessary condition for a suitable drug composition for in vivo use, is the sufficient content of medicine in a single unit dosage form. In a study by Yousefpour et al [22], a method for the synthesis of particles of DS–Dox NP, in the aqueous phase, was described. The method was simple; however, the drug concentrations in the resulting product were more than one order of magnitude less than those needed to create clinically applicable therapeutic systems (about 2 mg/mL in solutions for intravenous administration [40]).…”
Section: Resultsmentioning
confidence: 99%
“…One such substance is doxorubicin (Dox). In the work of Yousefpour and co-authors, it was shown that a simple mixing of DS and Dox led to the formation of a specific nanocomplex [22]. Xiaoyun and co-authors have obtained hydrogel from DS and Dox by adding Ca ions, and have studied the impact of these ions on the properties of the resulting product [23].…”
Section: Introductionmentioning
confidence: 99%
“…Dextran sulfate nanoparticles containing DOX can be formed by mixing the drug and polymer. 39 Nearly 100% encapsulation efficiency is achieved at a drug/dextran weight ratio of 0.5. In vitro release from these nanoparticles showed an initial rapid release of 14% over the first 24 hours and a total release of 32% through 15 days.…”
Section: Electrostatic Interactions and Ion Pairingmentioning
confidence: 99%